AN INFRARED AND 1H MAS NMR INVESTIGATION OF STRONG HYDROGEN BONDING IN USSINGITE, NA2ALSI3O8 (OH) - Johnson E.A.; Rossman G.R. (My University, 2004)
The mineral ussingite, Na_2AlSi_3O_8(OH), an “interrupted” tectosilicate, has strong hydrogen bonding between OH and the other nonbridging oxygen atom in the structure. Infrared spectra contain a strongly polarized, very broad OH-stretching band with an ill-defined maximum between 1500 and 1800 cm^(−1), and a possible OH librational bending mode at 1295 cm^(−1). The IR spectra confirm the orientation of the OH vector within the triclinic unit cell as determined from X-ray refinement (Rossi et al. 1974). There are three distinct bands in the ^1H NMR spectrum of ussingite: a predominant band at 13.5 ppm (TMS) representing 90% of the structural hydrogen, a second band at 15.9 ppm corresponding to 8% of the protons, and a third band at 11.0 ppm accounting for the remaining 2% of structural hydrogen. From the correlation between hydrogen bond length and ^1H NMR chemical shift (Sternberg and Brunner 1994), the predominant hydrogen bond length (H...O) was calculated to be 1.49 Å, in comparison to the hydrogen bond length determined from X-ray refinement (1.54 Å). The population of protons at 15.9 ppm is consistent with 5–8% Al–Si disorder. Although the ussingite crystal structure and composition are similar to those of low albite, the bonding environment of OH in low albite and other feldspars, as characterized through IR and ^1H NMR, is fundamentally different from the strong hydrogen bonding found in ussingite.
Keywords: Infrared spectroscopy; NMR spectroscopy; Ussingite; Low albite; Hydrogen